BEHAVIORAL RECORD OF MATING AND FEEDING OF Oxycheila tristis (COLEOPTERA: CARABIDAE) - de Castro Jacques , Gabriel; Dutra Barbosa, Leonardo; Magalhães de Souza, Marcos (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Behavioral, feeding, and reproductive record of Oxycheila tristis (Coleoptera: Carabidae: Cicindelinae) in a gallery forest in the municipality of Luminárias, Minas Gerais, Brazil. A copulating pair of beetles was observed, with the female simultaneously feeding on a male Atta sp. (Hymenoptera: Formicidae).